Implementation of Risk-Based Business Licensing Policy in Supporting Ease of Doing Business (Study in Ogan Ilir Regency) - Alhamdari, Lailita; Thamrin, Muhammad Husni; Mustain, Akhmad (Universitas Muhammadiyah Ponorogo, 2026)
Risk-Based Business Licensing isa response to the JobCreation Law aimed at improving the investment ecosystem, business activities, and the Ease of Doing Business (EoDB) in Indonesia. This study analyzes theimplementation of risk-based business licensing policies in Ogan Ilir Regency using Charles O. Jones' implementation theory, which includes three main aspects: organization, interpretation, and application. The research method usedis descriptive qualitative through interviews, observations, and documentation. The analysis results show that the implementation of risk-based business licensing policies in Ogan Ilir Regency has been running well, as reflected in the adjustment of the organizational structure and the formation of a licensing technical team, adequatehuman resources in the licensing service sector, adequate internet networks and facilities, and good coordination between DPMPTSP in Ogan Ilir Regency and the licensing technical team. However, several challenges were identified,including budget limitations whichhave implications for the lack of policy socialization and participation in face-to-face OSS RBA training, insufficientpublicunderstanding of theOSS RBA system itself,and supporting regulations for risk-based business licensing that are still in the drafting stageand havenot yetbeen ratified.Itis necessaryfor theRegional Government to strengthen the capacity and competence of human resources, encourage the availability of budget allocations for licensing services, encourage OPD participation to accelerate the preparation of supporting regulations for risk-based licensing, and expand access to assistance by utilizing digital services through simple video tutorials for business actors.It is recommended that future research conduct a comparative study between regions to analyze patterns and best practices in the implementation of risk-based business licensing policies in Indonesia, particularly in areas facing similar challenges. Additionally, future studies should adopt a quantitative approach to measure the policy's impact on business actors.